In vitro antioxidant and cholinesterase inhibitory activities of methanolic fruit extract of Phyllanthus acidus. Issue 1 (December 2015) - Moniruzzaman, Md.; Asaduzzaman, Md.; Hossain, Md.; Sarker, Jyotirmoy; Rahman, S.; Rashid, Mamunur; Rahman, Md.
Abstract Background Alzheimer's disease (AD) is a progressive neurodegenerative disorder clinically characterized by loss of memory and cognition. Cholinergic deficit and oxidative stress have been implicated in the pathogenesis of AD. Therefore, inhibition of acetylcholinesterase and oxidation are the two promising strategies in the development of drug for AD.Phyllanthus acidus, belonging to the family Euphorbiaceae, is a tree and has been used in traditional medicine to treat several pain, inflammatory and oxidative stress related disorders such as rheumatism, bronchitis, asthma, respiratory disorder, also important to promote intellect and enhance memory, thus supporting its possible anti-Alzheimer's properties. In this study, P. acidus was evaluated for its cholinesterase inhibitory and antioxidant activities. Methods In this study, we evaluated the antioxidant potential and neuroprotective activity ofP. acidus by assessing total phenol content (FCR assay), total flavonoid content, total antioxidant capacity, Fe 3+ reducing power capacity, DPPH (2, 2-diphenyl-1-picrylhydrazyl) and hydroxyl radical scavenging capacity, lipid peroxidation inhibition activity & metal chelating activity. In addition acetylcholinestrase (AChE) and butyrylcholinestrase (BChE) inhibitory activities were performed using Ellman's method. Results Total phenolic content and total flavonoid content of the extract were 116.98 mg of gallic acid equivalent and 168.24 mg of quercetin equivalent per gm of dried extract. The methanolic extract ofP. acidus (MEPA) showed considerable total antioxidant activity and reducing capacity. In DPPH scavenging assay and hydroxyl radical scavenging assay, the MEPA showed 84.33 % and 77.21 % scavenging having IC50 of 15.62 and 59.74 μg/ml respectively. In lipid peroxidation inhibition activity MEPA showed moderate inhibition of peroxidation at all concentrations with IC50 value of 471.63 μg/ml and exhibited metal chelating activity with IC50 value 308.67 μg/ml. The MEPA exhibited inhibition of rat brain acetylcholinesterase and human blood butyrylcholinesterase in a dose dependent manner and the IC50 value was found to be 1009.87 μg/ml and 449.51 μg/ml respectively. Conclusion These results of the present study reveal that MEPA has considerable amount of antioxidant activity as well as anti-acetylcholinesterase and anti-butyrylcholinesterase activity which suggest its effectiveness against Alzheimer's disease and other neurodegenerative disorders.